The Effect of Transformational Leadership and Integrity on Organizational Commitment and Its Impact on Employee Performance at The Brantas Sampean Watershed Management Center - Iswahyudi, Muhammad; Silitonga, P. Eddy Sanusi; Noor, M. Irawan (Dinasti International Journal of Management Science, 2025)
This study aims to determine and analyze the influence of 1) transformational leadership on employee performance, 2) integrity on employee performance, 3) organizational commitment on employee performance, 4) transformational leadership on organizational commitment, 5) integrity on organizational commitment, 6) transformational leadership on employee performance through organizational commitment, and 7) integrity on employee performance through organizational commitment. The study was conducted at the Brantas Sampean Watershed Management Center with a sample of 67 respondents. The sampling technique used was simple random sampling. The data analysis methods used descriptive analysis and path analysis. The results of the study indicate that: 1) transformational leadership has an effect on employee performance, 2) integrity has an effect on employee performance, 3) organizational commitment has an effect on employee performance, 4) transformational leadership has an effect on organizational commitment, 5) integrity has an effect on organizational commitment, 6) transformational leadership has no effect on employee performance through organizational commitment, and 7) integrity has an effect on employee performance through organizational commitment.